THE LIFESTYLE OF PHYSICAL EDUCATION FRESHMEN STUDENTS OF THE YEAR OF 2014.2 AT THE UNIVERSIDADE FEDERAL DO PIAUÍ, IN TERESINA (Fiep Bulletin - online, 2016)
The aim of the present study was to verify the lifestyle of students of physical education freshman in 2014, at the Universidade Federal do Piauí in Teresina. A sample of 43 college students with a mean age of 20,05 years (SD = 3,75). For data collection the Pentáculo do Bem Estar questionnaire was used to assess lifestyle, classifying them into positive behaviors (always, almost always) and negative behaviors (and sometimes never). The questionnaire addressed the key components that reveal the lifestyle of the individual, namely: nutrition, physical activity, preventive behavior, social relationships and stress management. In the data analysis we used descriptive statistics (mean, standard deviation, frequency and percentage). We conclude that dietary habits and physical activity are behaviors and health risk that can negatively contribute to the quality of life of college students. It is suggested that interventional measures aimed at improving the lifestyle of the college should address strategies in food control and preventive health care.
Keywords: Lifestyle; welfare; health.